Coupling spectroscopic and chromatographic techniques for evaluation of the depositional history of hydrocarbons in a subtropical estuary. (October 2015) - Martins, César C.; Doumer, Marta E.; Gallice, Wellington C.; Dauner, Ana Lúcia L.; Cabral, Ana Caroline; Cardoso, Fernanda D.; Dolci, Natiely N.; Camargo, Luana M.; Ferreira, Paulo A.L.; Figueira, Rubens C.L.; Mangrich, Antonio S.
Abstract: Spectroscopic and chromatographic techniques can be used together to evaluate hydrocarbon inputs to coastal environments such as the Paranaguá estuarine system (PES), located in the SW Atlantic, Brazil. Historical inputs of aliphatic hydrocarbons (AHs) and polycyclic aromatic hydrocarbons (PAHs) were analyzed using two sediment cores from the PES. The AHs were related to the presence of biogenic organic matter and degraded oil residues. The PAHs were associated with mixed sources. The highest hydrocarbon concentrations were related to oil spills, while relatively low levels could be attributed to the decrease in oil usage during the global oil crisis. The results of electron paramagnetic resonance were in agreement with the absolute AHs and PAHs concentrations measured by chromatographic techniques, while near-infrared spectroscopy results were consistent with unresolved complex mixture (UCM)/total n -alkanes ratios. These findings suggest that the use of a combination of techniques can increase the accuracy of assessment of contamination in sediments. Highlights: Historical inputs of hydrocarbons in a subtropical estuary were evaluated. Spectroscopic and chromatographic methods were used in combination. High hydrocarbon concentrations were related to anthropogenic activities. Low hydrocarbon levels could be explained by the 1970s global oil crisis. Abstract : Spectroscopic and chromatographic techniques could be used together to evaluate hydrocarbon inputs to coastal environments.